1999
DOI: 10.1002/(sici)1521-4141(199912)29:12<3925::aid-immu3925>3.0.co;2-s
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced susceptibility to cytotoxic T lymphocytes without increase of MHC class I antigen expression after conditional overexpression of heat shock protein 70 in target cells

Abstract: Antigenic peptides have been found associated with heat shock proteins (HSP) including cytoplasmic HSP70 and heat shock cognate protein 70 as well as the endoplasmic reticulum‐resident glucose‐regulated protein 94. Recently, HSP70 transfection has been reported to increase MHC class I cell surface expression and antigen presentation on mouse melanoma B16 cells (Wells et al., Int. Immunol. 1998. 10: 609). To analyze the effect of HSP70 on MHC class I cell surface expression and lysability of target cells we tra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
14
0

Year Published

2002
2002
2020
2020

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 28 publications
(15 citation statements)
references
References 47 publications
(54 reference statements)
1
14
0
Order By: Relevance
“…Moreover, stressed cells, e.g., virus-infected cells or tumor cells, appear to be usually a more appropriate target for cytotoxic effector cells of the immune system than unstressed cells (43). We have previously shown that HSP70, which is known to protect cells efficiently against various adverse conditions, fails to protect against specific cytotoxic effector mechanisms of CTL mediated in the granule exocytosis pathway (19,20,27). Thus, cytotoxic effector mechanisms of the cellular immune system seem to dominate over the protective stress response.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, stressed cells, e.g., virus-infected cells or tumor cells, appear to be usually a more appropriate target for cytotoxic effector cells of the immune system than unstressed cells (43). We have previously shown that HSP70, which is known to protect cells efficiently against various adverse conditions, fails to protect against specific cytotoxic effector mechanisms of CTL mediated in the granule exocytosis pathway (19,20,27). Thus, cytotoxic effector mechanisms of the cellular immune system seem to dominate over the protective stress response.…”
Section: Discussionmentioning
confidence: 99%
“…In the model of the human melanoma cell line Ge, we have shown previously that constitutive overexpression of the MHClinked stress-inducible HSP70 does not protect against apoptosis mediated by CTL in the granule exocytosis pathway (19). Acute HSP70 overexpression can even increase the susceptibility against CTL in vitro (19,20). The immune system appears to be able to kill target cells undergoing an otherwise protective stress response.…”
mentioning
confidence: 99%
“…The similarities between the requirements for costimulatory molecules and inflammatory cytokines in our model and that for cross-priming by hsp are so striking that it raises the intriguing possibility that priming by a whole cell vaccine may occur through the hsp representation pathways. In fact, overexpression of hsp70 on B16 melanoma cells not only induced MHC class I expression on the tumor cell surface, it also rendered the B16 melanoma immunogenic (73)(74)(75). Combining this with the capacity of hsp gp96 to induce IL-12 and TNF-␣ (70, 71) provides a possible pathway for CD4-independent cross-priming of tumor-reactive CD8 T cells by dendritic cells (76).…”
Section: Discussionmentioning
confidence: 99%
“…The chaperoned peptides can be channelled into the endogenous class I presentation pathway of a subset of professional antigen-presenting cells, which are then able to prime CD8-positive CTLs. Further, purified preparations of HSC70, gp96, HSP70, and calreticulin isolated from cancer cells have been shown to elicit cancer-specific immunity against a wide range of cancers in animal models (Tamura et al, 1997;Srivastava et al, 1998;Dressel et al, 1999;Robert et al, 2001;Udono et al, 2001). In this study, we have reported for the first time that HSC70 204 -212 ) were added to wells containing the 233 -241, capable of inducing HLA-B4601-restricted and tumourreactive CTLs from PBMCs of the six of 10 epithelial cancer patients tested.…”
Section: Discussionmentioning
confidence: 79%